SUCCESSFUL INTERVENTION: RAISING AWARENESS OF ADVANCED CARE PLANNING (ACP) IN THE RURAL COMMUNITY SETTING. Issue 2 (1st June 2013) - Weaver, E; Vaughan, T
Abstract : Background: In 2009 in the Barossa Valley, South Australia, a group formed to promote the Respecting Patient Choices Program and ACP in their community. The group represents nurses, (aged and acute sites), doctors, lawyers, Ministers of Religion, Justices of the Peace, Emergency Services and community members. Aim: To determine if active promotion of ACP has improved awareness and acceptance in the community Method: Data collected over a 4 year period to determine public awareness of ACP in our local community. Information collected included age, gender, existing ACP documents and their storage location. At the end of the 4 year period data collected was analysed to determine if the pro-active approach had been effective in the above stated areas. Results: Over 4 years the table shows a 100% increase of people with Advanced Care Plans. The unexpected positive outcome is the shift in awareness of ACP to younger age groups. Anecdotally people surveyed indicated an awareness of the Respecting Patient Choices branding and literature received through legal services, health services, medical centres and community avenues. Discussion: Direct contact with individuals has proven to be an effective way to promote community awareness and acceptance of ACP in the rural community. Conclusion: Data collected proves that active promotion of ACP with the community results in a positive change of attitude towards ACP—no longer a taboo subject.